PROFIL MIKROORGANISME PENYEBAB DERMATOFITOSIS DI RUMAH SAKIT ISLAM SULTAN AGUNG SEMARANG - Karyadini, Hesti Wahyuningsih; Rahayu, Rahayu; Masfiyah, Masfiyah (Media Farmasi Indonesia, 2018)
Fungal infections due to dermatophytes are often referred to as "Tinea". There are 3 genus which causes of dermatophytosis, among others are Trichophyton sp, Epidermophyton sp and Microsporum sp. The purpose of this study was to find out the profile of dermatophytosis-causing microorganisms in all patients in Sultan Agung Islamic Hospital Semarang. Samples are all patients with diagnosis of suspected dermatophytosis in Sultan Agung Islamic Hospital Semarang period January 2016 - December 2016. This research was descriptive research with Cross Sectional design. The sample was all patients with diagnosis of suspected dermatophytosis at Sultan Agung Islamic Hospital Semarang period January 2016 - December 2016. Research phase starting from pre analytic, analytic and post analytic stage. The results showed that the percentage of patients with dermatophytosis was more prevalent in female patients (53%) than in men (47%). Most dermatophytosis patients with tinea corporis diagnosis were 35% and tinea capitis was 29%, while for tinea pedis was 21%, tinea cruris was 12% and tinea unguium was 3%. The most dermatophyte fungi isolated are Microsporum canis 32%, Trichophyton mentagrophytes 18%, Microsporum audiounii 6%, Trichophyton rubrum 3%, Trichophyton tonsurans 3%. Microsporum canis is the most cause of dermatophytosis in Sultan Agung Islamic Hospital, Semarang.